2022
DOI: 10.3390/molecules27031138
|View full text |Cite
|
Sign up to set email alerts
|

The Biological Fate of Pharmaceutical Excipient β-Cyclodextrin: Pharmacokinetics, Tissue Distribution, Excretion, and Metabolism of β-Cyclodextrin in Rats

Abstract: β-cyclodextrin has a unique annular hollow ultrastructure that allows encapsulation of various poorly water-soluble drugs in the resulting cavity, thereby increasing drug stability. As a bioactive molecule, the metabolism of β-cyclodextrin is mainly completed by the flora in the colon, which can interact with API. In this study, understanding the in vivo fate of β-cyclodextrin, a LC-MS/MS method was developed to facilitate simultaneous quantitative analysis of pharmaceutical excipient β-cyclodextrin and API de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Experiments reported that a fraction between 10% and 20% of administered β-CD is digested in the small intestine after 24 h. 63,64 Major degradation of β-CD occurs in the microflora of the intestine or colon. 55,64 β-CD also showed a trend towards renal enrichment, 55 . We thank all members of the Holland group for helpful discussions and continuous support.…”
Section: Small-animal Pet Imaging and Biodistribution Studiesmentioning
confidence: 94%
See 2 more Smart Citations
“…Experiments reported that a fraction between 10% and 20% of administered β-CD is digested in the small intestine after 24 h. 63,64 Major degradation of β-CD occurs in the microflora of the intestine or colon. 55,64 β-CD also showed a trend towards renal enrichment, 55 . We thank all members of the Holland group for helpful discussions and continuous support.…”
Section: Small-animal Pet Imaging and Biodistribution Studiesmentioning
confidence: 94%
“…49,50 Further hydrolysis results in smaller molecules, mainly maltotriose, maltose, and glucose, which are eventually absorbed and metabolised into CO 2 and H 2 O. [51][52][53][54][55] Known CD-hydrolysing enzymes include cyclomaltodextrinases and a-amylases. 49,50 Chemical conditions, including low pH with Brønsted acids, or the use of Lewis acids, were also reported to catalyse the hydrolytic ring-opening of CDs.…”
Section: Small-animal Pet Imaging and Biodistribution Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclodextrins are generally not metabolizable by gastric acids or amylase. When CDs are administered orally, it was observed that CDs rapidly hydrolyze in the intestine and get excreted via feces ( Mu et al, 2022 ). While in parenteral administration, the primary excretion of CDs occurs via urine ( Loftsson et al, 2016 ).…”
Section: Cyclodextrins and Their Advantagesmentioning
confidence: 99%
“…Therefore, inclusion technology may be an effective strategy to improve the low water solubility of DHM. Particularly, the hydroxypropyl-β-cyclodextrin (HP-β-CD) not only has the good properties of β-cyclodextrin (β-CD) such as low price and good safety but also has the characteristics of biodegradability and high solubility (Mu et al., 2022 ). Ruan et al.…”
Section: Pharmaceutical Designs Of Dhmmentioning
confidence: 99%